2003
DOI: 10.1113/eph8802507
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Steroid Hormones on the Transcription of Genes Encoding Enzymes of Oxidative Phosphorylation

Abstract: The energy production of a cell is tuned to its needs. Most of the energy requirements are met by oxidative phosphorylation taking place in the respiratory chain of the mitochondria and approximately 90 % of the oxygen is consumed there. Depending on the challenge, the oxidative capacity can slightly increase or can vary over an order of magnitude, the mitochondria reacting accordingly with either subtle changes in the activity of OXPHOS, with an increased biosynthesis of some of the OXPHOS subunits, or with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 57 publications
(79 reference statements)
2
70
1
1
Order By: Relevance
“…Strigolactones could also first target mitochondrial or cytoplasmic receptors, as do thyroid hormones in mammalian cells that stimulate mitochondrial biogen- esis, lipid catabolism, and respiration (Scheller and Sekeris, 2003;Weitzel et al, 2003). It was also proposed in the seed of the parasitic Orobanche that strigolactones bind plasmalemma receptors, establishing a covalent link (Humphrey and Beale, 2006).…”
Section: The Mitosis Of G Rosea Is Also Stimulated In Response To Gr24mentioning
confidence: 99%
“…Strigolactones could also first target mitochondrial or cytoplasmic receptors, as do thyroid hormones in mammalian cells that stimulate mitochondrial biogen- esis, lipid catabolism, and respiration (Scheller and Sekeris, 2003;Weitzel et al, 2003). It was also proposed in the seed of the parasitic Orobanche that strigolactones bind plasmalemma receptors, establishing a covalent link (Humphrey and Beale, 2006).…”
Section: The Mitosis Of G Rosea Is Also Stimulated In Response To Gr24mentioning
confidence: 99%
“…In case, however, this ROS inactivating process is compromised, ROS accumulate with deleterious effects on DNA (mutations) and on other macromolecules, leading to reduced ATP availability and increased oxidative stress, activation of the mitochondrial permeability transition pore and initiation (77). Thus, the regulation of the energetic requirements of the cell is a crucial process, involving a pleiade of agents (22), necessitating a tight coordination of mitochondrial functions with those of other cell compartments (21,22,26,(78)(79)(80)(81).…”
Section: The Role Of Steroid and Thyroid Hormone Receptors In Mitochomentioning
confidence: 99%
“…The steroid and thyroid hormones also exert rapid effects by way of membrane bound receptors-classical, G-protein associated, or still unidentified molecules (7)(8)(9)(10) resulting in modulation of membrane, cytoplasmic, and/or nuclear associated processes (11). The detection of steroid and TRs in mitochondria of a variety of cells raised the question as to the role of these agents in mitochondrial physiology and in the coordination of processes necessitating the involvement of both nuclear and mitochondrial actions (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…GR phosphorylation at S226 results in inhibition of the GR function, possibly due to increased GR nuclear export and is a result of JNK activation [80,89,97,98]. Finally, phosphorylation of GR at S404 attenuates GR signalling and is due to GSK3 kinase activation [99]. We have recently reported that differential GR phosphorylation in the resistant CEM-C1-15 versus sensitive CEM-C7-14 ALL cells modulates GR transcriptional activity and target selectivity resulting in diverse pro-or anti-apoptotic Bcl-2 family members' gene expression in the two cell lines [58].…”
Section: Post-translational Modificationsmentioning
confidence: 99%